Lateral pedicle graft for the treatment of isolated tooth recession - Shikha Sharma (SRM Journal of Research in Dental Sciences)
Gingival recession is defined as the apical migration of the gingival margin from its normal position leading to exposure of the root surface. It not only poses problems in maintaining good oral hygiene but also simultaneously hampers the esthetics. In the present case, the patient came up with a complaint of a denuded root surface due to apical migration of the gingival margin and also a complaint of sensitivity in the same. The case was diagnosed as chronic generalized gingivitis with localized periodontitis in relation to 31. Based on the clinical outcomes, the lateral pedicle graft (LPG) technique was performed. A complete coverage of the exposed root surface was achieved. This case report shows that a simple technique of root coverage like LPG can result in the successful coverage of the denuded root surface.